Studying the Effects of Contamination on Soil Properties Using Remote Sensing (Journal of Engineering, 2014)
The problem of soil contamination is increased recently due to increasing the industrial wastes such as petroleum hydrocarbon, organic solvents, and heavy metals as well as maximizing the use of agricultural fertilizers. During this period, wide development of data collection methods, using remote sensing techniques in the field of soil and environment applications appear and state the suitable technique for remediation. This study deals with the application of remote sensing techniques in geoenvironmental engineering through a field spectral reflectance measurements at nine spots of naturally hydrocarbons contaminated soil in Al-Daura Refinery Company site which is located to the south west of Baghdad using radiometer device to get standard curves of wavelengths and analyzing the satellite imagery of the site to get the spectral reflectance curves using GIS technique and EARDAS software package which help in producing thematic maps for the spatial distribution and concentration of contaminants. The comparison of results showed a good correlation between the spectral reflectance from field measurements and the spectral reflectance obtained from analyzing the satellite imagery. The study also improves a method to save cost, time, efforts and staff.